SAFETY OF FOOD PRODUCTS IN THE CONTEXT OF THE DISCIPLINE «COMMODITY OF FOOD PRODUCTS» (Innovative professional education, 2023)
The article updates the importance of food safety regulations in the postsecondary education process for food technology majors. The main xenobiotics and contaminants of food raw materials and products are presented. The relevance of acquired competences in the assessment of integral food safety in the production activity of professional junior bachelors is indicated.
Keywords: safety of food raw materials and food products, xenobiotics and contaminants, Codex Alimentarius, HACCP, food legislation in the educational process